The Tagus estuary (Portugal) during the 8th – 5th BC: stage of transformation and construction of identity - Sousa, Elisa de (2016)
The earliest Iron Age phase in the Tagus estuary (late 8th-6th century BCE, in traditional chronology) engaged a highly diversified range of active agents who took part in the area’s orientalization process: local Late Bronze Age communities, western Phoenician settlers and possibly also native elements from southern Iberia. Each of these groups sustains a heterogeneous formation that derives from differentiated social, economic and cultural status played by their constituents, and that is, unfortunately, very dificult to distinguish in terms of the available archaeological evidence. However, we believe that it is possible, at least to some degree, to trace their different cultural markers, and try to understand the role played by each of these agents in the formation of a unique identity sphere that will characterize the central western Atlantic coast of Iberia during the 1st millennium BCE.